Influence of Body Mass Index (BMI) on Mother’s Health during Pregnancy and Fetal Outcomes - Abid, Mahrukh; Tehreem Yazdani; Naveen Sheikh; Hadia Chaudhry; Irum Mehmood; Zubariya Tahir (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the influence of body mass index in obese and normal weight mothers regarding pregnancy and fetal outcomes and to study the predicting factors. Study Design: Case-control study. Place and Duration of Study: Department of Gynaecology and Obstetrics, Pak Emirate Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2023. Methodology: Pregnancy outcomes, medical and obstetric history, and demographic information of the mother were gathered. Weight at last prenatal appointment minus weight before pregnancy or self-reported data at delivery were used to determine gestational weight gain (GWG). Obese women were placed in Group-A, whereas normal weighted women were placed in Group-B. Results: A total of four hundred (n=400) pregnant women were included in this study, out of which, 2(0.5%) were underweight, 320(80.0%) were normal weight, 16(4.0%) were overweight, 62(15.5%) were obese. Mean age was 32.87±6.77 years. Group-A had more gestational diabetes (n=12, 19.3%). Similarly, gestational hypertension, preeclampsia, dystocia were seen more in Group-A as compared to Group-B (p<0.05). Moreover, induced labor (32.3% vs 16.3%), failed induction of labor (11.3% vs 1.6%), augmentation of labor (33.9% vs 29.1%), Cesarean delivery (40.3% vs 28.1%) rates were significantly increased in Group-A. Six (9.7%) obese women delivered babies that had APGAR score ≤7 after 5 minutes. Conclusion: The risks of prenatal hypertension, preeclampsia, gestational diabetes, labour dystocia, labour induction, unsuccessful induction of labour, large-for-gestational-age infants, and Cesarean birth are greatly elevated in mothers who are overweight during their pregnancies.